Αριστοφάνης - Αριστοφάνης, π. 450-π. 385 π.Χ. (100 αθάνατα έργα ;, 1951)
Αχαρνής -- Ιππής -- Νεφέλαι -- Σφήκες -- Ειρήνη -- Όρνιθες -- Λυσιστράτη -- Θεσμοφοριάζουσαι -- Βάτραχοι -- Εκκλησιάζουσαι -- Πλούτος